2022
DOI: 10.2319/112021-854.1
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular retromolar space in adults with different sagittal skeletal patterns: Cone-beam computed tomography analysis

Abstract: Objectives To analyze the mandibular retromolar space among normal-divergent adult patients with different sagittal skeletal patterns by cone-beam computed tomography (CBCT). Materials and Methods CBCTs of a total of 120 normal-divergent adult patients were investigated. Patients were categorized into the following three groups according to their ANB angle: skeletal Class I (48 patients), skeletal Class II (36 patients), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 21 publications
(42 reference statements)
1
14
0
Order By: Relevance
“…Similarly, the comparison of the cortical bone thicknesses between different sites within the subgroups did not show statistically significant differences, except for the comparison within the hypo-subgroup at the M0 vs. M4 sites. Interestingly, descriptive statistics in the subgroups revealed greater cortical bone thicknesses in subjects with hypo-divergency, which aligns with the previous literature [4,23,[28][29][30]. This indicates the influence of facial morphology on mandibular cortical bone thickness [31].…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, the comparison of the cortical bone thicknesses between different sites within the subgroups did not show statistically significant differences, except for the comparison within the hypo-subgroup at the M0 vs. M4 sites. Interestingly, descriptive statistics in the subgroups revealed greater cortical bone thicknesses in subjects with hypo-divergency, which aligns with the previous literature [4,23,[28][29][30]. This indicates the influence of facial morphology on mandibular cortical bone thickness [31].…”
Section: Discussionsupporting
confidence: 90%
“…10 While Fan's study reported signi cantly larger RMS in Class III group compared to other groups. 11 This discrepancy may be due to the variation of samples used in these studies. Thus, distalizing the upper and lower dentition with TAD at the same time can be used to relieve the mild to moderate crowding and maintain the molar relationship in Class I patients.…”
Section: Discussionmentioning
confidence: 91%
“…A recent CBCT study which measured the RMS in normodivergent subjects with similar methods as ours also found shorter RMS in Class II group. 11 However, other studies reported that RMS was not related to the sagittal skeletal class but the vertical facial patterns 4,18 .This discrepancy may be due to the fact that vertical facial patterns have more prominent effect on the RMS compared to sagittal classes 18 . This result was well in line with previous two-dimensional study which suggested that skeletal classes were related to the morphology of the mandible, especially mandibular body length.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…For adult patients without growth potential, the limit for available distance is closer to the apical level 23 . Patients with Class III malocclusion have greater retro-molar space than Class II and Class I patients along the posterior line of occlusion 24,25 . Retro-molar distance showed a decreasing tendency as the mandibular plane angle increased 26 .…”
Section: Discussionmentioning
confidence: 95%